Podocnemis expansa (Schweigger, 1812) (Reptilia, Testudines, Podocnemidae): exotic species in the State of Pernambuco, Northeast Region of Brazil - dos Santos, Ederjow; Rameh-de-Albuquerque, Luciana Carla; Zanotti, Alexandre Pinheiro; Pereira, Edivania do Nascimento; Santos, Ednilza Maranhão dos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
In June and December 2013, the presence of adult individuals of the Amazon turtle (Podocnemis expansa) and their spawning were attested through direct observation, in a protected area located in the municipality of Recife, state of Pernambuco, Brazil, which is a region where the species is exotic.